Faktor-Faktor Yang Mempengaruhi Kepuasan Masyarakat Dalam Program Jaklingko - Yanti Apriyani; Hajarudin Hajarudin; Aep Saefullah; Ika Agustina; Moh. Tahang; Siska Dwi Rahayu; Imelda Krisanti; Melati Suci Anjar Kusuma (Lembaga Pengembangan Kinerja Dosen, 2024)
This study aims to determine what are the factors that become community satisfaction in the jaklingko program. DKI Jakarta is an area whose population is growing rapidly, the more the population the more transportation there is. Therefore, the gevornment needs an integrated transportation system, one of which is Jaklingko, one of the programs in DKI Jakarta. The population in this study are people or consumers who use the services of jaklingko transportation, especially city transportation on the Andara-Blok M route. The data collection technique uses the interview method by conducting in-depth interviews with 6 informants with different ages and professions. Anlysis technique used is qualitative method. The result showed a positive effect. Community satisfaction is proven that the use of jaklingko transportation is very helpful, starting from the price to the services provided.